2004
DOI: 10.1590/s0102-311x2004000400027
|View full text |Cite
|
Sign up to set email alerts
|

The impact of health-management training programs in Latin America on job performance

Abstract: A study was undertaken in Mexico, Colombia, and El Salvador to determine the impact of a management training program on health managers' job performance. A quasi-experimental design was used where in the baseline study an intervention group of 85 district health managers in the three countries was compared with a control group of 71 managers who did not receive the training program. After the implementation of an 18-month training program (which included 5-day training workshops and a series of tasks to be car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 8 publications
0
9
0
1
Order By: Relevance
“…In alignment, Seims et al found that strengthening leadership and management skills among DHMs in Kenya through a team-based approach led to significant increases in health-service delivery [24]. The importance of building abilities among DHMs to work effectively within teams has been confirmed by other studies as well [5,10,23,43,54], and an emphasis on this should thus be ensured in district level management strengthening efforts.…”
Section: District Management Capacity and Its Association With Healthmentioning
confidence: 95%
See 1 more Smart Citation
“…In alignment, Seims et al found that strengthening leadership and management skills among DHMs in Kenya through a team-based approach led to significant increases in health-service delivery [24]. The importance of building abilities among DHMs to work effectively within teams has been confirmed by other studies as well [5,10,23,43,54], and an emphasis on this should thus be ensured in district level management strengthening efforts.…”
Section: District Management Capacity and Its Association With Healthmentioning
confidence: 95%
“…state, regional, district, sub-district), is frequently perceived as a way to improve health system performance as local authorities are better able to make informed decisions regarding local conditions [1][2][3]. However, in order to improve performance, individual capacity among local health managers are needed [1,[4][5][6]. Moreover institutional capacities, such as functional support systems and enabling work environments, including an appropriate level of autonomy for the managers', must be in place [7].…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1980s, management strengthening interventions (MSIs) have had a predominant focus on strengthening the DHMs' individual competencies rather than the system capacity (13)(14)(15)(16). Individual competencies among DHMs are indeed critical for them to carry out their job in an effective and efficient way (3,13,14,(17)(18)(19)(20)(21)(22)(23)(24)(25). Nevertheless, it has been posed that leadership and management within complex adaptive systems, such as the district health system, need to be considered as more than the act of individuals, and rather as something that emerges through an interplay of many interacting forces (26).…”
Section: Introductionmentioning
confidence: 99%
“…2 Collaborative programs or educational partnerships between such institutions and healthcare organizations are increasingly common in low-income settings and locations without easy access to similar training programs. [8][9][10][11] Educational partnerships can be implemented fairly quickly and may be more cost-effective than establishing an academic program from scratch. Bradley et al suggest that Ministries of Health could play a role in funding access to such partnership programs.…”
Section: Changing Who and How We Train And Educatementioning
confidence: 99%